New Records of Algae in Shaqlawa District, Erbil, Kurdistan Region of Iraq - J. Toma, Janan; H. Aziz, Farhad (Al-Nahrain Journal of Science, 2021)
Monthly samples of algae collected in eighteen sites of springs and streams through September-2019 till August-2020during morning till afternoon in Shaqlawa district within Erbil Province, Kurdistan Region of Iraq. Eleven various kinds of algae were identified for first time in Iraqi inland water, distributed to three genera of blue-green algae, which include Marssoniella elegans, Pseudoanabaena catenata, Cyanotheca aeroginosa, also in Pyrrophyta identified four new species genera include Gymnodium inversum, Woloszynskia tenuissima, Peridinium goslaviense, Hemidinium naustum and Xanthopyta recorded three species were Ophiocytium arbuscula, Ophiocytium parvulum, Tetraedriella polychloris while Cryptophyta only have one species was Cryptomonas reflex. According to physicals and chemicals characteristics, water temperature varied from 14.942 oC to 18.475 oC, pH lies on alkaline side of neutrality, electrical conductivity ranged between (627.472-2092.306 ms/cm) and high concentration of salinity recorded in Azarian spring, higher value of calcium and magnesium recorded in Azarian and Benwan springs were 294.84 mg/L and 106.578 mg/L respectively. Lower value of nitrate and phosphate reported in Sard and Piawan springs, while lower value of sulfate observed in Prenga spring.